Ascertaining Human Emotions using Blue Eyes Technology - Kanagalakshmi, T. Kohila; Vibha, S; Prathibha, KH (International Journal of Computer Sciences and Engineering, 2025)
Blue eyes technology aims to create computational machines which can sense and understand human feelings and emotions. It uses camera, microphone and various sensors to recognize human actions and emotions and aid disabled people. There are many researches in this area, still they have some limitations. In this paper we have proposed on architecture for blue eyes technology which can identify human emotions through facial features and sensors such as Galvanic skin response sensor, heart pulse sensor, temperature sensor. This paper explores various image processing techniques such as noise removal, segmentation, image enhancement. Supervised classification technique such as artificial neural network with back propagation is used to predict emotions. This research involves many areas like Machine learning, Image processing and IoT.